Genomics role at the identification of patients with inborn errors of immunity - Yepes, Nathalie (2023)
Primary immunodeficiencies or inborn errors of immunity are disorders affecting adaptive and/or innate immunity in the absence of a precipitating cause, with a predominantly genetic etiology. These pathologies predispose to recurrent infections, autoimmune diseases, oncological diseases, etc. We present the case of a pediatric patient who has a history of repeated urinary infections, generalized lymphadenopathy, myositis, without syndromic phenotype, no neurocognitive compromise, in multidisciplinary and pharmacological management with little response, and immuno-rheumatological, infectious extension studies often fail to provide a specific diagnosis. Due to the complexity of such cases, a targeted genetic study was initiated, involving the sequencing of a gene panel associated with immunodeficiencies, utilizing Next-Generation Sequencing (NGS) methodology. The genetic study revealed a clinically significant, probably pathogenic, heterozygous variant in the TNFRSF13B gene, which is associated with common variable immunodeficiency. Advancements in diagnosis through genomic studies now enable the establishment of phenotype/endotype/genotype connections. This facilitates specific diagnoses, the implementation of targeted and personalized therapeutic options, prediction of reactions, and long-term follow-up. Genetic counseling is also crucial. This approach aligns with the principles of 6P medicine with emphasis on precision, prevention, participation, prediction, personalization in order to be able to do it at the population level. It enables the development of curative target therapies aimed at reducing the morbidity and mortality associated with these hereditary, debilitating, and chronic conditions